Molecular Diagnosis of Genital Chlamydia trachomatis Infection by Polymerase Chain Reaction (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):362-365 The abstract of this article is available on the PubMed website